An Oral Discourse Perspective on Second Language Learning - Iwan Jazadi (IJEE (Indonesian Journal of English Education), 2015)
Teaching and learning to speak English using oral language data drawn from real life communication can be unique experiences for English teachers and students who usually rely on unauthentic written texts of a textbook. This small study focuses on a conversation involving the author and his native speaker counterpart. Entities of the conversation put under analysis and discussion include its register and generic structure, exchanges, prosodic features and communication strategies. The dialogic features of the text are presented in the data collection procedure and description section. The article is expected to provide a perspective for doing similar analysis with other oral data by teachers and advanced learners of English as a second or foreign language. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v2i2.3092